2015
DOI: 10.1093/alcalc/agv129
|View full text |Cite
|
Sign up to set email alerts
|

Orexin in Patients with Alcohol Dependence Treated for Relapse Prevention: A Pilot Study

Abstract: Orexin or its receptor is a potential target for relapse prevention treatment, but further study with long-term observation is needed to verify the usefulness of blood orexin determination as a marker of alcohol relapse risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…There has been a small number of reports relating AUDs and the ORX system in human patient populations. Blood samples taken from human patients with alcohol dependence exhibited elevated ORX in early withdrawal (Bayerlein et al 2011; Ziolkowski et al 2016) and these elevated levels were correlated with depression-like symptoms in that timeframe (von der Goltz et al 2011). Thus there appears to be some association with human AUDs and the ORX system, although further work is clearly warranted.…”
Section: The Hypocretin/orexin System and Alcoholmentioning
confidence: 99%
“…There has been a small number of reports relating AUDs and the ORX system in human patient populations. Blood samples taken from human patients with alcohol dependence exhibited elevated ORX in early withdrawal (Bayerlein et al 2011; Ziolkowski et al 2016) and these elevated levels were correlated with depression-like symptoms in that timeframe (von der Goltz et al 2011). Thus there appears to be some association with human AUDs and the ORX system, although further work is clearly warranted.…”
Section: The Hypocretin/orexin System and Alcoholmentioning
confidence: 99%
“…These neurons exist in the hypothalamus while having projections throughout the brain, and they are known to be involved in promoting substance abuse and related behaviors, including ethanol consumption as well as arousal, anxiety, motivation and stress (DiLeone et al, 2003;Li et al, 2014). This hcrt system is related to AUD, as shown by evidence in humans that blood hcrt levels are elevated in alcohol-dependent individuals during the early stages of withdrawal (Bayerlein et al, 2011;Ziółkowski et al, 2016) and are positively correlated with depression-like symptoms of alcohol withdrawal (von der Goltz et al, 2011). Hcrt expression is also shown to be stimulated by ethanol in adult rats (Moorman et al, 2016;Barson & Leibowitz, 2017) and by prenatal exposure to ethanol (Chang et al, 2012;Chang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Upon measurement, the alcohol-dependent patients showed significantly higher levels of blood ORX than the control group. However, after 4 weeks of abstinence the levels of ORX decreased significantly similar to the levels of ORX in control subjects, suggesting that ORXR1 are potential target for the relapse prevention treatment and that ORX is a biomarker of alcohol relapse (Ziotkowski et al, 2016). Previous studies from von der Goltz et al, showed the involvement of ORX in the regulation of stress, affectivity and addictive behavior.…”
Section: Novel Aud Medications and Their Signaling Pathwaysmentioning
confidence: 93%